2007
DOI: 10.1161/01.atv.0000282199.66398.8c
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Peripheral Arterial Disease: A Dark Corner in Vascular Biology

Abstract: Abstract-Peripheral arterial disease (PAD) is characterized by reduced blood flow to the limbs, usually as a consequence of atherosclerosis, and affects Ϸ12 million Americans. It is a common cause of cardiovascular morbidity and an independent predictor of cardiovascular mortality. Similar to other atherosclerotic diseases, such as coronary artery disease, PAD is the result of the complex interplay between injurious environmental stimuli and genetic predisposing factors of the host. Genetic susceptibility to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 169 publications
4
59
1
1
Order By: Relevance
“…This study is still in the screening stage and needs a replication study using an independent panel of cases (PAD patients) and controls in the future. To date, several genes susceptible to PAD have been reported in a case-control study with sample sizes ranging from ~100 to 1300 subjects 7) , but we could not confirm these genes as candidate genes in our study. Thus, we speculate that our genome-wide association study still cannot cover all the genes for PAD.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This study is still in the screening stage and needs a replication study using an independent panel of cases (PAD patients) and controls in the future. To date, several genes susceptible to PAD have been reported in a case-control study with sample sizes ranging from ~100 to 1300 subjects 7) , but we could not confirm these genes as candidate genes in our study. Thus, we speculate that our genome-wide association study still cannot cover all the genes for PAD.…”
Section: Discussioncontrasting
confidence: 68%
“…Despite its prevalence and the high social cost attributed to PAD 6) , the genetic basis of PAD and the factors that determine its responsiveness to treatment are yet to be understood. There are no genetic tests available that reliably identify the subset of subjects carrying inherited risk factors for developing PAD on a large scale 7) ; however, three family studies to date have reported estimates of heritability of PAD and thus its heritability could be suggested [8][9][10] . A logical next step is to perform a more comprehensive and unbiased scan of variations in all genes or in the entire genome using what is commonly referred to as a genome-wide association study (GWAS).…”
Section: Introductionmentioning
confidence: 99%
“…34 Genes encoding for interleukin-6 (IL-6), fibrinogen (FGB) and intercellular adhesion molecule-1 (ICAM-1) have been reported to be associated with PAD risks. 35 The present study showed that both ANRIL and BRAP are risk genes for lower ABI values. In addition to the main effects of BRAP and ANRIL, we also demonstrated an additive effect of these 2 genes on ABI.…”
Section: Discussionsupporting
confidence: 55%
“…10 Recently, Knowles and colleagues reviewed what is known of the genetic susceptibility to PAD and concluded that our understanding of the genetic basis of PAD is quite limited. 11 Neither linkage analysis nor linkage associations studies have convincingly uncovered any genes that either identify patients at risk for PAD or predict their clinical course. The major weakness of these published studies is the small number of patients studied.…”
Section: Article P 1207mentioning
confidence: 99%